Three-dimensional adaptive optical nanoscopy for thick specimen imaging at sub-50-nm resolution - Hao, Xiang; Allgeyer, Edward S.; Lee, Dong-Ryoung; Antonello, Jacopo; Watters, Katherine; Gerdes, Julianne A.; Schroeder, Lena K.; Bottanelli, Francesca; Zhao, Jiaxi; Kidd, Phylicia; Lessard, Mark D.; Rothman, James E.; et al. (Nature methods, 2021)
Understanding cellular organization demands the best possible spatial resolution in all three dimensions. In fluorescence microscopy, this is achieved by 4Pi nanoscopy methods that combine the concepts of using two opposing objectives for optimal diffraction-limited 3D resolution with switching fluorescent molecules between bright and dark states to break the diffraction limit. However, optical aberrations have limited these nanoscopes to thin samples and prevented their application in thick specimens. Here we have developed an improved iso-stimulated emission depletion nanoscope, which uses an advanced adaptive optics strategy to achieve sub-50-nm isotropic resolution of structures such as neuronal synapses and ring canals previously inaccessible in tissue. The adaptive optics scheme presented in this work is generally applicable to any microscope with a similar beam path geometry involving two opposing objectives to optimize resolution when imaging deep in aberrating specimens. The combination of adaptive optics with an improved isoSTED nanoscope allows imaging of cells and tissues with sub-50-nm isotropic resolution.